Aging-Associated Differences in Epitranscriptomic m6A Regulation in Response to Acute Cardiac Ischemia/Reperfusion Injury in Female Mice - Su, Xuan; Shen, Yan; Jin, Yue; Kim, Il-man; Weintraub, Neal L.; Tang, Yaoliang (Frontiers in Pharmacology, 2021)
Elderly patients are more susceptible to ischemic injury. N6-methyladenosine (m6A) modification is the most abundant reversible epitranscriptomic modification in mammalian RNA and plays a vital role in many biological processes. However, it is unclear whether age difference impacts m6A RNA methylation in hearts and their response to acute myocardial ischemia/reperfusion (I/R) injury. In this study, we measured the global level of m6A RNA methylation as well as the expression of m6A RNA “writers” (methylation enzymes) and “erasers” (demethylation enzymes) in the hearts of young and elderly female mice undergone sham surgery or acute MI/R injury. We found that m6A RNA level and associate modifier gene expression was similar in intact young and old female hearts. However, young hearts show a significant reduction in m6A RNA while elderly hearts showed only a slight reduction in m6A RNA in response to acute I/R injury. To explore the mechanism of differential level of m6A RNA modification, we use qRT-PCR and Western blotting to compare the mRNA and protein expression of major m6A-related “writers” (Mettl3, Mettl14, and WTAP) and ‘erasers” (ALKBH5 and FTO). Mettl3 mRNA and protein expression were significantly reduced in both young and elderly hearts. However, the levels of FTO’s mRNA and protein were only significantly reduced in ischemic elderly hearts, and age-related downregulation of FTO may offset the effect of reduced Mettl3 on reduced m6A RNA level in the hearts of aging mice hearts with acute I/R injury, indicating aging-related differences in epitranscriptomic m6A regulation in hearts in response to acute I/R injury. To further investigate specific I/R related targets of Mettl3, we overexpressed Mettl3 in cardiomyocyte line (HL1) using a lentiviral vector, and the m6A enrichment of Bcl2, Bax, and PTEN were quantified with m6A RIP-qPCR, we found that m6A modification of PTEN mRNA decreased after in vitro hypoxia/reperfusion injury (iH/R) while Mettl3 augments m6A levels of both Bax and PTEN after iH/R, indicating that Bax and PTEN are target genes of Mettl3 under iH/R stress.